On the Spectrum of an Equivariant Extension of the Laplace Operator in a Ball - Burskii, V. P.; Shtepina Т. V. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We study the relationship between the well-posedness of an equivariant problem for the Poisson equation in a ball and the spectrum of the operator generated by it.